Sensations induced by medium and long chain triglycerides: role of gastric tone and hormones. Issue 1 (1st January 2000) - Barbera, R; Peracchi, M; Brighenti, F; Cesana, B; Bianchi, P A; Basilisco, G
Abstract : BACKGROUND: The relative roles of gastric relaxation and the neuroendocrine signals released by the small intestine in the perception of nutrient induced sensations are controversial. The different effects of long chain (LCT) and medium chain (MCT) triglyceride ingestion on perception, gastric relaxation, and hormonal release may help to elucidate the mechanisms underlying nutrient induced sensations. AIMS: To compare the effects of intraduodenal LCT and MCT infusions on perception, gastric tone, and plasma gut hormone levels in healthy subjects. SUBJECTS: Nine fasting healthy volunteers. METHODS: The subjects received duodenal infusions of saline followed by LCTs and MCTs in a randomised order on two different days. The sensations were rated on a visual analogue scale. Gastric tone was measured using a barostat, and plasma gut hormone levels by radioimmunoassay. RESULTS: LCT infusion increased satiation scores, reduced gastric tone, and increased the levels of plasma cholecystokinin, gastric inhibitory polypeptide, neurotensin, and pancreatic polypeptide. MCT infusion reduced gastric tone but did not significantly affect perception or plasma gut hormone levels. LCTs produced greater gastric relaxation than MCTs. CONCLUSIONS: The satiation induced by intraduodenal LCT infusion seems to involve changes in gastric tone and plasma gut hormone levels. The gastric relaxation induced by MCT infusion, together with the absence of any significant change in satiation scores and plasma hormone levels, suggests that, at least up to a certain level, gastric relaxation is not sufficient to induce satiation and that nutrient induced gastric relaxation may occur through cholecystokinin independent mechanisms.